An IFN-STAT Axis Augments Tissue Damage and Inflammation in a Mouse Model of Crohn's Disease - Stolzer, Iris; Dressel, Anja; Chiriac, Mircea T.; Neurath, Markus F.; Günther, Claudia (Frontiers in Medicine, 2021)
Blocking interferon-function by therapeutic intervention of the JAK-STAT-axis is a novel promising treatment option for inflammatory bowel disease (IBD). Although JAK inhibitors have proven efficacy in patients with active ulcerative colitis (UC), they failed to induce clinical remission in patients with Crohn’s disease (CD). This finding strongly implicates a differential contribution of JAK signaling in both entities. Here, we dissected the contribution of different STAT members downstream of JAK to inflammation and barrier dysfunction in a mouse model of Crohn´s disease like ileitis and colitis (Casp8ΔIEC mice). Deletion of STAT1 in Casp8ΔIEC mice was associated with reduced cell death and a partial rescue of Paneth cell function in the small intestine. Likewise, organoids derived from the small intestine of these mice were less sensitive to cell death triggered by IBD-key cytokines such as TNFα or IFNs. Further functional in vitro and in vivo analyses revealed the impairment of MLKL-mediated necrosis as a result of deficient STAT1 function, which was in turn associated with improved cell survival. However, a decrease in inflammatory cell death was still associated with mild inflammation in the small intestine. The impact of STAT1 signaling on gastrointestinal inflammation dependent on the localization of inflammation, as STAT1 is essential for intestinal epithelial cell death regulation in the small intestine, whereas it is not the key factor for intestinal epithelial cell death in the context of colitis. Of note, additional deletion of STAT2 was not sufficient to restore Paneth cell function but strongly ameliorated ileitis. In summary, we provide here compelling molecular evidence that STAT1 and STAT2, both contribute to intestinal homeostasis, but have non-redundant functions. Our results further demonstrate that STATs individually affect the distinct pathophysiology of inflammation in the ileum and colon respectively, which might explain the diverse outcome of JAK inhibitors on inflammatory bowel diseases.